Analysis Perspectives from local view: Logics of violence in a toledan village (1936-1942) - Benayas Sánchez, David (Hispania Nova, 2021)
This paper aims to profile a work itinerary for research related to local history, case studies and the memory of traumatic historical events. From the framework of analysis of ethnomethodology for memorial accounts and supporting in the interpretation of documentary sources and the recent bibliographic production it is intended to analyze from a microhistorical perspective the trace that the rebels´ violence system left in an individual and his family, the impact that violence perpetrated during the war and the post-war period had on people, and the logics and dynamics emanating from local areas.
Keywords: logic; dynamics; social control; repression; memory